Hemodynamic Changes of Hepatic & Renal Vessels in Systemic Bacterial Infection with Fever in HCV Related Cirrhosis - Helal, Eman M.; Sharaf-Eldin, Mohamed; Abou El Azm, Abdel Raouf; Badr Eldin, Nagwa Mansour; Dawoud, Mohammed Mahmoud; Abd-Elsalam, Sherief; Ziada, Dina Hazem (Infectious Disorders - Drug Targets, 2020)
Objectives: To study the hemodynamic changes of hepatic & renal vessels in systemic bacterial infection with fever in HCV related cirrhosis with possible complications. Methods: Three groups of patients with systemic bacterial infection with fever were included in the study; group Ц#134; included 15 patients with decompensated cirrhosis, group Ц#134;Ц#134; included 15 patients with compensated cirrhosis and group Ц#134;Ц#134;Ц#134; included 10 patients without liver affection. Laboratory parameters and Doppler US of hepatic and renal vessels were evaluated during and after subsidence of fever in all patients. Results: Forty patients were enrolled in this prospective study. There were 22 male and 18 female patients. We found that the direction of blood flow in the portal and splenic veins was hepatopetal and the veins were non pulsatile in all cases with no change during and after subsidence of infection. There was no significant difference in portal or splenic vein diameters during and after subsidence of infection in the three studied groups. However, the mean values of portal and splenic veins peak velocities were significantly lower during infection in cirrhotic groups. The mean value of hepatic artery resistive index during fever was significantly higher than after fever in cirrhotic groups. Renal resistive and pulsatility indices were significantly higher during fever in cirrhotic groups. Conclusion: Systemic bacterial infection with fever can affect hepatic haemodynamics leading to aggravation of portal hypertension and increasing the risk of complications as variceal bleeding and hepatic encephalopathy and can also affect renal haemodynamics with increased risk of renal impairment.
Keywords: encephalopathy